Comparative Analysis of Solar Power Plants Using Direct Sunlight and Glass Reflected Light - Muhammad Renaldy; Rahmaniar, Rahmaniar; Parlin Siagian (INFOKUM, 2025)
Indonesia has the potential for new and renewable energy (EBT), including solar energy as a source of power generation. Energy efficiency can be defined as the ratio between the electrical power generated and the input power received. Low efficiency impacts the electrical power output of solar modules. This underlies the use of Solar Power Plants (PLTS) as a new and renewable electrical energy source to replace fossil fuels that have limited quantities and pollute the environment. Solar cells as PLTS units have the constraint of insufficient output power and are highly dependent on natural conditions. One method of optimizing solar cells is by using sunlight-reflecting glass (reflectors). Sunlight is a renewable energy source that can be utilized as a new power generator. However, in the process, certain additions are required to the solar cell module to optimize the output voltage produced. Efforts to optimize electrical output in solar modules by maximizing the intensity of light falling on the surface of the solar module by using direct sunlight. The results obtained are in the form of a comparison.